Degradation and transformation pathways of sulfamethazine by pre-oxidation disinfection process. Issue 2 (April 2022) - Lin, Yingzi; Zhou, Mingliang; Wang, Gaoqi; Li, Hao; Wei, Yuhang; Lou, Yi; Zhang, Dongyan; Ji, Li
Abstract: Sulfamethazine (SMZ) is a pollutant that exists widely in the water environment, and it poses a threat to the environment and human health. However, the traditional water treatment process has very limited ability to remove SMZ. This paper studies the effectiveness of NaClO to remove SMZ after K2 FeO4 /O3 pre-oxidation and explores the main ways of chlorination degradation of SMZ. It also studies the influence of factors, such as the dosage of different pre-oxidants, chlorination time, NaClO dosage, pH, fulvic acid and Br - on the removal effect of SMZ. The results show that pre-oxidation process of O3 and K2 FeO4 significantly increases the degradation rate of subsequent chlorinated SMZ, and the degradation rate of SMZ increases by 10.49% and 8.41% separately after pre-oxidation. When the pH value of the system is neutral, the three processes have the best degradation effect on SMZ. Among them, the O3 -NaClO process has the highest degradation rate of SMZ, up to 98.69%. FA can inhibit both the degradation rate and the degradation rate of SMZ in O3 /K2 FeO4 -NaClO system, and has the most obvious inhibition on the degradation of SMZ by O3 preoxidation, and the degradation rate decreases by 13.58%. The rise of Br - concentration will promote the efficiency of NaClO alone to oxidize SMZ, but will inhibit the chlorination degradation rate after pre-oxidation of O3 /K2 FeO4 . The main pathways to chlorinate and degrade SMZ lie in the substitution of chlorine for amino groups to promote SMZ ring opening, intra-molecular Smiles-type rearrangement, and the subsequent desulfurization reactions. Graphical Abstract: ga1 Highlights: The effect of Fulvic Acid on the degradation of Sulfamethazine by O3 /NaClO process is greater than K2 FeO4 /NaClO process. Bromide can promote the degradation of Sulfamethazine by NaClO, but will inhibit the O3 /K2 FeO4 -NaClO processes. The main pathway in chlorinated degradation of Sulfamethazine is Smile-type rearrangement. Three processes achieved the highest efficiency in degrading Sulfamethazine near pH neutral.